EVALUASI STRATEGI PENINGKATAN MUTU DAN KESELAMATAN PASIEN DI RUMAH SAKIT X YOGYAKARTA - Sundoro, Totok; Sari, Desi Wulan; Alvionita, Indah; Nuhuyanan, Wirda Rahim; Bafadhal, Annisah (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2023)
The quality of health services is a guarantee for the community to obtain an optimal degree of health. There are still incidents in the hospital in Semester I of 2020, namely 4 (four) cases of unexpected incidents, 2 (two) cases of almost injury, 12 (twelve) cases of non-injury and 12 (twelve) cases of Potential Injury. In order to improve the quality of patient care and ensure patient safety, the hospital needs to have a strategy for improving the quality and patient safety that reaches all work units in the hospital. Objective: To evaluate strategies for improving the quality & patient safety at Hospital X. Data collection techniques used interview guidelines and observation sheets as instruments. Interviews were conducted with the Leader or Management, the Quality and Patient Safety Committee, the PPI Committee and staff. Interviews were conducted to find out regulations and efforts to improve quality and patient safety as well as to find obstacles faced by hospitals in their implementation. Observation and documentation activities related to the implementation of strategies carried out in an effort to improve the quality of patient safety in hospitals. The validity of the data was analyzed by triangulation technique. The implementation of the strategy to improve the quality of patient safety at Hospital X Yogyakarta refers to the National Standard for Hospital Accreditation 1stEdition. The implementation is good but there are still obstacles and shortcomings in supporting the strategy that has been implemented by the hospital. It is necessary to revise the director's policy regarding reporting time, provide new employee training education on data management systems and five mandatory trainings that support quality programs, information technology support in managing quality data, as well as achievement-oriented leadership styles to build commitment and monitoring strategies that can be used as methods monitoring in the implementation of patient safety efforts. Hospital X Yogyakarta has a strategy in improving the quality of patient safety through revision of the director's policy on quality data reporting, staff education in implementing quality programs, providing information technology support in quality data management and implementing management functions in patient safety quality management.